Using Algebraic Tiles from Secondary Mathematics Kit - Chaurasia, P. K. (JOURNAL OF INDIAN EDUCATION, 2019)
The Secondary Mathematics Kit developed by National Council of Educational Research and Training (NCERT) describes and elaborates an important and effective pedagogical strategy at the secondary stage, whose potential is rarely exploited yet, which promotes active engagement in subjects, respectively. It arises from a perspective that mathematics is a constructive activity and is most richly learned when learners are actively constructing objects, relations, questions, problems and meanings. In these kits, we show that not only can all learners perform conceptual activities, but the act of construction or activity can engage learners who might otherwise be passive and uninterested. Kit describes a range of practices for producing the examples that generally illustrate, model and demonstrate concepts. We claim that the experiments or activities that learners perform arise from a pool of ideas. Several concepts through these kits can be explored, enriched and extended—a pedagogical focus that is a powerful way of understanding the concepts. Teachers find ways to transfer initiative to learners to experiment with activity or construct mathematical objects, extending their sophistication and deepening their understanding. In this article, we perform the activities based on algebraic tiles along with secondary stage students of KV No. 1, Ajmer. We show that not only all learners can perform conceptual activities, but also the act of construction or activity can engage learners who might otherwise be passive and uninterested. We observe that activities provide ways to reveal learners’ depth and breadth of understanding of concepts and general strategies for creating engaging and concept-deepening questions. It is surprising how learners can be energised and intrigued by simple adjustments to standard classroom algebraic tasks.